2007
DOI: 10.1128/aac.01487-06
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Current Cefepime Breakpoints To Predict Clinical Outcomes of Bacteremia Caused by Gram-Negative Organisms

Abstract: For commonly encountered gram-negative bacilli, a MIC of cefepime of 8 g/ml or less was defined by the Clinical and Laboratory Standards Institute as "susceptible" prior to the commercial release of the antibiotic. We assessed 204 episodes of bacteremia caused by gram-negative organisms for which patients received cefepime (typically 1 to 2 g every 12 h) as the primary mode of therapy. The cefepime MIC breakpoint derived by classification and regression tree (CART) software analysis to delineate the risk of 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
88
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 9 publications
3
88
0
Order By: Relevance
“…A classification and regression tree (CART) analysis conducted in their study revealed that a cefepime MIC of Ն8 mg/liter was associated with increased mortality (58.4% compared to 21.4%, P ϭ 0.001), despite the fact that an MIC of 8 mg/liter was considered susceptible at the time of the study (13). Tam and colleagues (14) evaluated outcomes in patients with Pseudomonas aeruginosa bacteremia with reduced susceptibility (defined as an MIC of 32 to 64 mg/liter) to piperacillin-tazobactam, and the susceptibility breakpoint was Յ64 mg/liter at the time of the study.…”
Section: Discussionmentioning
confidence: 99%
“…A classification and regression tree (CART) analysis conducted in their study revealed that a cefepime MIC of Ն8 mg/liter was associated with increased mortality (58.4% compared to 21.4%, P ϭ 0.001), despite the fact that an MIC of 8 mg/liter was considered susceptible at the time of the study (13). Tam and colleagues (14) evaluated outcomes in patients with Pseudomonas aeruginosa bacteremia with reduced susceptibility (defined as an MIC of 32 to 64 mg/liter) to piperacillin-tazobactam, and the susceptibility breakpoint was Յ64 mg/liter at the time of the study.…”
Section: Discussionmentioning
confidence: 99%
“…The CLSI recommends using the highest doses of CFP originally approved by the FDA for empirical therapy of febrile neutropenia to treat organisms with a MIC of 8 g/ml (2 g i.v. q8h) (20,21). However, PK/pharmacodynamics (PD) analysis in children was required to define the appropriate dosing regimen for GNB with a MIC of 4 or 8 g/ml, realizing that children will often have greater renal clearance of ␤-lactams than adults.…”
Section: Discussionmentioning
confidence: 99%
“…For young infants older than 30 days with greater CFP CL values, Monte Carlo simulation shows that the FDA-approved usual maximum dosage regimen of CFP, 50 mg/kg q8h infused over 30 min, did not provide a sufficient attainment rate of 60% TAM for organisms with a MIC of Ն8 g/ml. Based on several reports indicating a poor prognosis of infections caused by organisms with a higher CFP MIC (20,32), there is clearly a need to revise the treatment options for infections caused by these organisms. On the other hand, sufficiently high target attainment rates were observed for neonates with a relatively low CFP CL with infections caused by organisms with a MIC of 8 g/ml.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inappropriate empirical antimicrobial-based therapy and delays to initiate appropriate antimicrobial-based therapy are both detrimental to patient outcome. 34 Authors have described failure of cefepime-susceptibility breakpoints to predict clinical outcomes 35 as well as the requirement of achieving adequate drug exposure to be successful in treating patients with P. aeruginosa infections. 36 Additionally, a multivariate logistic regression analysis demonstrated P. aeruginosa infection to be independently associated with treatment failure in cefepime-patients.…”
Section: Discussionmentioning
confidence: 99%